Ketika Konten Bicara: Eksplorasi Dampak Ewom Dan Customer Innovativeness Terhadap Adopsi Produk Baru - Kurniawan, Sabda Aji; Togatorop, Ervan (Universitas Bunda Mulia, 2025)
The digital transformation has significantly shifted consumer behavior, with electronic word of mouth (eWOM), particularly in the form of short videos (vWOM), becoming a primary source of information influencing new product adoption decisions. This study aims to examine the influence of eWOM on the intention to adopt new products, with customer innovativeness as a mediating variable, in the context of the adventure tourism destination Cakadiditrip in Ambon City. Using a quantitative approach and Structural Equation Modeling (SmartPLS 4.0), the study involved 97 respondents who had been exposed to Cakadiditrip’s video content on social media. The results show that eWOM significantly influences both the intention to adopt new products and customer innovativeness, and that customer innovativeness mediates the relationship between eWOM and adoption intention. These findings highlight the strategic importance of digital content marketing that aligns with the innovative traits of target audiences. Practical implications suggest that businesses, especially in emerging tourism sectors, should optimize vWOM as a persuasive communication tool to accelerate market innovation adoption.